Progresifisme Nilai-Nilai Risalah Islam Berkemajuan: Studi Implementasi Dakwah Kultural Di Universitas Muhammadiyah Gombong - Akbar, Tian Khusni; Atmojo, Ahmad Muslih (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to explore and analyze the implementation of cultural da'wah based on the values of the Progressive Islamic Treatise at the University of Muhammadiyah Gombong. Progressivism in this context refers to adaptation and renewal efforts in the delivery of da'wah, by emphasizing the application of Islamic values that are relevant to the needs of the times and local contextualization. This research method uses a qualitative approach with data collection techniques through field studies and documentation studies related to da'wah activities on campus. The findings of the study show that the implementation of cultural da'wah at the University of Muhammadiyah Gombong has shown progressivity in responding to the challenges of the times, with the integration of the values of the Progressive Islamic Treatise which includes moderation, inclusivity, and openness to differences. This study also identifies the Relevance of Cultural Da'wah in the Framework of Progressive Islamic Treatises, Implementation Strategies and Supporting and Inhibiting Factors in the Implementation of Cultural Da'wah, as well as providing strategic recommendations for optimizing the implementation of cultural da'wah in the university environment from the perspective of Progressive Islamic Treatises. The results of this research are expected to contribute to the development of a more effective cultural da'wah model in accordance with advanced and contextual Islamic values.